Improving compliance and evaluating physician–patient concerns in glaucoma: a pilot study - Mohannad Albdour; Aaron Shi; Chuhan Wang; Ibrahim Saleh; Karanjit S Kooner (Academia Medicine)
Purpose: To improve glaucoma treatment compliance via education, medication reminders, and understanding of patient and physician concerns. Patients and methods: We selected 194 consecutive eligible patients diagnosed with primary open-angle glaucoma or ocular hypertension (OHT) at a single academic center (92 men and 102 women) for this study. All 194 eligible patients were interviewed regarding glaucoma knowledge, medication usage, concerns, and fears. They were counseled and given educational handouts that focused on patients’ forgetfulness, self-efficacy, and lifestyle. The patients were reinterviewed after 4 weeks of the intervention. An independent group of sixteen glaucoma specialists were also surveyed regarding their concerns for their glaucoma patients. Results: In this study, patients aged 65 years, or more were more compliant than those <65 years (76% vs 50%, p < 0.05). In follow-up interviews of 125 (64%) patients, our method of intervention increased patient compliance from 77% to 94% (p < 0.05), which is much higher than the reported compliance rates in the United States ranging from 28% to 60%. In addition, patients’ major fear was becoming dependent on others (p < 0.05), while physicians were more concerned about patients’ ability to administer eye drops and understanding of instructions (p < 0.05). Conclusion: We found that patients aged 65 or more were more compliant, and our intervention improved patient compliance to 94%, which is higher than the nationally reported rates. In addition, the disparity between patient and physician fears suggests that communication barriers must be addressed to improve patient care.